The Role of The Government in Enforcing Mining Rehabilitation Laws: Environmental Law and Mining Law - Sudi Haryansyah; Rachmadi Usman; Muhammad Ananta Firdaus (International Forum of Researchers and Lecturers, 2025)
Mining activities in Indonesia result in significant environmental degradation, necessitating a robust legal framework for post-mining rehabilitation. However, enforcement is often hindered by normative overlaps between the Mining Law (No. 3/2020) and the Environmental Law (No. 32/2009), alongside a